Towards deep-UV surface-enhanced resonance Raman spectroscopy of explosives: ultrasensitive, real-time and reproducible detection of TNT1. Issue 16 (21st August 2015) - Jha, Shankar K.; Ekinci, Yasin; Agio, Mario; Löffler, Jörg F.
<x xml:space="preserve">Abstract</x> We report ultrasensitive and label-free detection of 2, 4, 6-trinitrotoluene (TNT) deposited by drop coating using deep-ultraviolet surface-enhanced resonance Raman scattering (DUV-SERRS).